Register features in Formula One motorsport commentary: A study of the 2021 Abu Dhabi Grand Prix - Alif Rafsanjani; Adam Damanhuri (Privietlab, 2026)
This study examines the register features used in the English commentary of the Formula One Abu Dhabi Grand Prix 2021. Despite the growing body of research on sports discourse, Formula One commentary remains underexplored from a register perspective, particularly in relation to the linguistic features that characterize live motorsport broadcasting. Employing a qualitative descriptive approach, the study analyzes English-language commentary from the official Formula One broadcast using the Register-Functional framework proposed by Biber et al. (2022). The findings indicate that the commentary belongs to the Spoken Broadcast Commentary register and is realized through four register features: technical, descriptive, evaluative, and expressive. Technical features are the most frequent, reflecting the commentators' need to communicate specialized racing terminology, strategies, and regulations accurately during live broadcasts. Descriptive features narrate unfolding race events, while evaluative and expressive features are employed selectively to emphasize decisive moments and convey the significance of key developments. These findings demonstrate how different register features work together to fulfill the communicative demands of live Formula One commentary, extending the application of register analysis to motorsport discourse and contributing to the broader study of language variation in sports broadcasting.